Creating a model to develop self-sustainable aquaculture agribusiness enterprises in South Africa - Brown-Webb, Bernadette (University of the Free State, 2023)
South Africa’s policies emphasize the importance of small enterprise and aquaculture sector development in meeting development goals. Public and private investments do not have the expected impacts on enterprise development and job creation, and enterprise sustainability remains low. Many start-ups receiving support, including public funding, fail to become self-sustainable after the financial support ends. This study hypothesized that the development of self-sustainable aquaculture enterprises is not adequately supported by the enabling environment for the sector. The research objectives were to (1) determine the impacts of key stakeholders on enterprise development; (2) identify critical success factors for enterprises; (3) understand the impacts of the COVID-19 pandemic on the sector; (4) understand the challenges that compromise development of self-sustainable enterprises; and (5) develop and validate an enterprise development model to create self-sustainable aquaculture enterprises. The study was conducted in Saldanha Bay, in the Western Cape Province on South Africa’s west coast. A multiple-case study approach was followed, focusing on the marine bivalve shellfish farming industry. Semi-structured interviews were conducted with the owners or managers of ten aquaculture enterprises in Saldanha Bay, and with nine representatives of key role players in the sector. Consultations with enterprise development experts and stakeholder focus groups were also conducted. The mussel farming sector has a well-developed commercial value chain. Vertical integration is prominent, and 32% of farms have access to 51% of the farming area. Self-sustainable enterprises had minimum farm sizes of 15 ha, produced for at least 5 years, had a commercial focus and strong leadership. In-depth analysis of four case studies indicated success factors as having commercial focus, good management and leadership, access to finance, economies of scale, and perseverance. Key aquaculture stakeholders had positive and negative impacts on aquaculture sector development. Role players listed the main impacts as the approach to enterprise development (56%), community-based/co-operative ventures (67%) and impacts of different mandates (44%). Enterprise respondents listed community-based/co-operative ventures (50%), impacts of different mandates (40%) and the enabling environment (60%). Recommendations include resourcing of aquaculture industry associations, developing a focused aquaculture enterprise and supplier development (ESD) strategy and programme, streamlining application processes, and finalising the Oceans Economy Master Plan, to include aquaculture specific legislation. Both enterprise and role player respondent groups described critical success factors as environmentally sustainable farming (80% and 78%), addressing economic challenges/opportunities (90% and 89%) and good business leadership and management (100% each). Recommendations include a focused aquaculture development programme such as an incubator, a market development mechanism and an integrated research and development programme. Enterprise respondents listed the main areas of COVID-19 impacts on operations and production (100%), requirements to survive and rebuild (89%), factors promoting resilience (78%) and initiatives to prepare and rebuild (67%). Role player respondents listed impacts on the sector (100%), requirements to survive (89%), factors promoting resilience (78%) and support measures (67%). Recommendations include interventions to rebuild a more resilient sector, follow-up assessments, prioritising interventions for surviving enterprises, and developing an industry-based Business Continuity Strategy. The key factors affecting mussel production were a supportive regulatory framework, favourable environmental and economic conditions, appropriate species and technologies, and efficient farm and enterprise management. Challenges affecting these factors were identified and used to develop an aquaculture enterprise development model (AEDM) that could develop self-sustainable enterprises. The AEDM includes a vision for the sector, a mechanism for implementation, an aquaculture incubator, an integrated research and development programme, and a market development mechanism. The study recommends the implementation of a pilot AEDM in the Saldanha Bay Aquaculture Development Zone (ADZ). This will allow for testing of assumptions and refining of the model before rolling it out to other ADZs or industries.
Thesis (Ph.D.(Sustainable Agriculture))--University of the Free State, 2023
Keywords: Aquaculture; Agribusiness; Enterprise development model; Enterprises - Self-sustainable; Institutional framework; Support systems; Mussel farming; Case study methodology; Mussel culture; Agricultural industries; Case method